Research Results on Vibration Movement in Longitudinal-Vertical Plane of the Device Leveler that Form Soft Layer on the Field Surface of Wide-Range Chisel-Cultivator - Abdusalim Tukhtakuziev; Bobir Bozorovych Rajabov (Researchparks Publishing, 2022)
Developed comprehensive chisel-cultivator in effort to level the surface on the field and create a soft soil layer on it was specified in the article. The device is designed composing the levelers that consists of soil pushing plates and roller-crushers. Levelers are connected through hinges to transverse and longitudinal brushes of central and side sections of chisel-cultivator by means of parallelogram mechanisms, and roller-crushers by means of pulling devices. In order to ensure smooth leveling of field surface, the vibrating movement of device leveler in the longitudinal-vertical plane was researched. In this case, differential equation of forced vibrations of leveler was formulated and solved using the theory of vibrations and the basic laws of higher mathematics. According to obtained results, leveling of the field surface at required level by device leveler is achieved due to the correct selection of its mass and deviation angle of longitudinal pulling devices of the parallelogram mechanisms from horizon. In the work process, if it is ensured that longitudinal pulling devices of the parallelogram mechanisms occupy horizontal position or close to it, amplitude of vertical vibrations of leveler will have a minimum value and there will be achieved qualitative leveling of the field surface.